Imperial College of Tropical Agriculture, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
Exterior view of the building housing the Imperial College of Tropical Agriculture. It is located in St. Augustine, Trinidad and was used to provide training in Tropical Agriculture for West Indian and British Commonwealth students.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--St. Augustine; Architecture--Trinidad and Tobago; Universities and colleges--Trinidad and Tobago; Agricultural colleges--Trinidad and Tobago; ICTA; Imperial College of Tropical Agriculture, The